Intracranial Venous Pressures Manometry for Patients With Idiopathic Intracranial Hypertension: Under Awake Setting or General Anesthesia - Guo, Xin-bin; wei, Sen; Guan, Sheng (Frontiers in Neurology, 2019)
Background and Purpose: Venous sinus stenting (VSS) is a well-acknowledged treatment strategy for patients with a high venous sinus pressure gradient across the site of outflow obstruction. It is not clear whether intracranial venous pressure manometry should be performed awake or under general anesthesia (GA). The aim of this study is to compare the accuracy of venous manometry performed under GA or awake setting, and to evaluate stenting candidates to be determined under awake setting or under GA. Methods: The manometry results of 32 patients with idiopathic intracranial hypertension (IIH) were recorded under awake setting and general anesthesia before stenting. Mean venous pressures (MVPs) and trans-stenosis pressure gradients were obtained and compared between awake setting and general anesthesia status. Results: MVPs and trans-stenosis pressure gradients of 32 patients under GA and awake pressure setting were recorded. MVPs in the superior sagittal sinus, torcula, and transverse sinus were lower in the GA group, without statistical significant difference (P > 0.05). MVPs were significantly higher in the sigmoid sinus and jugular bulb under GA group (p < 0.05). Mean trans-stenosis pressure gradient was significantly lower in the group under GA (p < 0.05). Conclusions: Intracranial venous pressure seems to be affected by different levels of consciousness. Our study reveals that intracranial venous pressure is lower under general anesthesia than in the awake setting, which may have a potential impact on patient selection for venous sinus stenting.